The Effect of Labor Unions and Company Management on Employee Welfare in the Mediation of the Work Environment at Pt Transportasi Jakarta - Pradana, Kemal; Pasaribu, Bomer; Subagja, Iwan Kurniawan (The Institute of Academic Research and Publication (IARP), 2022)
This study aims to: 1) analyze the effect of trade unions and company management on the work environment 2) analyze the effect of trade unions and company management on employee welfare, 3) analyze the effect of the work environment on employee welfare, 4) analyze the influence of trade unions and company management on employee welfare. employee welfare through the work environment. The research was conducted at PT Transport Jakarta with a research sample of 95 employees. The sampling technique used was simple random technique. The data analysis method used descriptive analysis and path analysis. The results showed that: 1) there was an influence of trade unions and company management on the work environment, 2) there was an influence of trade unions and company management on employee welfare, 3) there was an influence of the work environment on employee welfare, 4) the work environment did not play a role in improving employee welfare. trade unions and company management on the welfare of employees at PT Transport Jakarta.